PENGORGANISASIAN KELOMPOK SWADAYA MASYARAKAT EKONOMI MIKRO BERBASIS PEREMPUAN (Studi Deskriptif Di Desa Pesanggrahan) - Jannah, Andita Uzlifatil; Mulyono, Joko Mulyono (Jurnal ENTITAS SOSIOLOGI, 2018)
The problem of unemployment is triggered by low opportunities for employment and our numerous human resources, especially in rural areas. Additionally, because of the limitations of traditional customs or some village that distinguishes between men and women into new problems that women are not allowed to work after marriage, they are entirely taken care of home and family only. It is very detrimental for women who ideally want to work to help improve the economy of the family. Therefore it takes empowerment for women and awareness through a self-help group for women could also have economic activities without having to leave her duties as a housewife. The theoretical framework of this research is that liberal feminism gender theory which based on freedom and equality of women. This research uses a qualitative method by using purposive sampling. Data collected through observation, interview, and documentation. The result of this research is that women's empowerment can do business with micro-scale to help improve family income; additionally, this research also explains about equality between women and men, and forms of women?s participation, democracy, transparency, and accountability in the following program. Keyword: Self-help groups, Gender equality, the Government program